Lutheran Conversion and Confessional Contact in Augsburg - Gray, Emily Fisher ca. 20./21. Jh. (Journal of Early Modern Christianity, 2025)
Lutherans and Catholics lived alongside one another peaceably as neighbours and shared political power in Early Modern Augsburg. Yet cases of conversion from one confession to the other were rare. Augsburg’s Lutherans and Catholics seldom changed confession even though they interacted regularly in domestic spaces, in public markets and taverns, and even in churches. Lutheran fears of recatholicization and Catholic concerns about minority status built confessional boundaries after 1555, making conversion socially disruptive. After 1648, under a new government based on confessional parity, conversion threatened to upset the political order as well. Neighbourliness and peaceful confessional coexistence in Augsburg depended on clear divisions between Catholics and Lutherans, making conversion a threat not only to the soul of the convert, but to the civic order of Augsburg.